IMPLENTASI MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA MEDIK DI RUMAH SAKIT BERDASARKAN UU NO. 36 TAHUN 2009 TENTANG KESEHATAN - Lina Herlina (2021)
This researc is intended to find out how to implement mediation in hospitals as an alternative to resolve medical disputes between doctors and patients. In serving the community, doctors provide services and actions according to science and competencies obtained through tiered education and a code of ethics that serves the community. In health services, sometimes the results provided by health workers and hospitals are not satisfactory or unsatisfactory to patients, such as lack of information provided and even negligence, resulting in medical disputes between patients, health workers and hospitals. In the resolution of a medical dispute between patients, health workers and hospitals, as we know in Law No.36 of 2009 on Health in Article 29, it is stated that medical dispute resolution takes precedence first through "Mediation". In discussing this problem, the method or methodology in this study uses legal normative with a normative juridical approach, and in collecting data using secondary data. From the results of the discussion, it was found that some of the unsuccessful implementation of mediation in the field was caused by several factors, for this reason it needs to be further discussed and reorganized regarding mediation in its specific statutory regulations in the health law.